ASSW2021 Science Conference Book of Abstracts - Canário, João; Vieira, Gonçalo; Pina, Pedro; Baptista, Joana; Folhas, Diogo; Freitas, Pedro; Miranda, Vasco; David, Ana Salomé (Zenodo, 2021)
Book of abstracts of the Science Conference of the Arctic Science Summit Week 2021, held online from 23 to 26 March 2021. Website: http://www.assw2021.pt